Anatomical study on some species of genus Cyperus in northern Iran - Mehrvarz, Saeidi S.; Moharami, E. (Український ботанічний журнал, 2016)
Comparative anatomy of six taxa of Cyperus distributed in the north of Iran was studied. The investigated
species are: C. difformis, C. distachyos, C. fuscus, C. pygmaeus, C. odoratus subsp. transcaucasicus, and C. rotundus.
Cross sections of stems and leaves of these species were examined. The following characters were determined to be
taxonomically informative: cross-section shape of the aerial stem, presence or absence of vascular bundle in the central
part of stem cross-sections, the diameter of mesophyll and air cavities in stem and leaf cross-sections. Cyperus fuscus and
C. difformis differ from other studied species in having large air cavities in stem and leaf cross section. Our results show
that comparative anatomy of lateral stems and leaves may provide additional characters to be considered in taxonomic
studies within this genus. Проведене порівняльне вивчення анатомії шести таксонів роду Cyperus, поширених на півночі Ірану: C. difformis,
C. distachyos, C. fuscus, C. pygmaeus, C. odoratus subsp.
transcaucasicus і C. rotundus. Досліджували поперечні зрізи стебел і листків цих видів. Таксономічно важливими
визначені такі ознаки: форма поперечного зрізу повітряного стебла, наявність або відсутність судинного пучка
в центральній частині поперечних зрізів стебла, діаметр
мезофіла і повітряних порожнин в поперечних зрізах
стебел і листя. Cyperus fuscus і C. difformis відрізняються
від інших вивчених видів наявністю великих повітряних
порожнин в поперечних зрізах стебел і листків. Наші
результати показують, що порівняльна анатомія бічних
стебел і листків може забезпечити додаткові ознаки для
таксономічних досліджень цього роду. Проведено сравнительное изучение анатомии шести таксонов рода Cyperus, распространенных на севере Ирана:
C. difformis, C. distachyos, C. fuscus, C. pygmaeus, C. odoratus
subsp. transcaucasicus и C. rotundus. Исследовали поперечные срезы стеблей и листьев этих видов. Таксономически важными определены следующие признаки: форма
поперечного среза воздушного стебля, наличие или отсутствие сосудистого пучка в центральной части поперечных срезов стебля, диаметр мезофилла и воздушных
полостей в поперечных срезах стеблей и листьев. Cyperus
fuscus и C. difformis отличаются от других изученных видов наличием больших воздушных полостей в поперечных срезах стеблей и листьев. Наши результаты показывают, что сравнительная анатомия боковых стеблей
и листьев может обеспечить дополнительные признаки
для таксономических исследований этого рода.